(untitled) (The Review of Diabetic Studies, 2024)
Rising rates of uncontrolled diabetes mellitus highlight the urgent need for effective patient education strategies that strengthen self-care practices and prevent complications. Structured teaching interventions have emerged as a practical approach for enhancing patient knowledge, particularly in settings where awareness levels remain low. The present investigation evaluated the effectiveness of a structured teaching programme on self-care management among adults with uncontrolled diabetes attending the Endocrinology Outpatient Department of NRI General Hospital, Chinakakani, Guntur District, Andhra Pradesh. Employing a pre-experimental onegroup pretest–posttest design, the study included 60 participants aged 31 years and above, selected through non-probability convenient sampling. Data were gathered using a structured questionnaire that assessed sociodemographic characteristics, general diabetes-related information, and knowledge across 45 self-care items. Following the pretest, participants received a structured teaching programme that addressed diet, physical activity, medication adherence, healthcare follow-up, lifestyle modifications, and management of complications through visual and interactive teaching aids. A posttest administered after 15 days demonstrated a substantial improvement in knowledge, with adequate knowledge increasing from 0% in the pretest to 61.6% in the posttest. Mean knowledge scores rose from 18.8±11.45 to 37.8±7.24, and the paired t-test (t=3.465, p<0.05) confirmed statistically significant improvement. Chi-square analysis showed meaningful associations between posttest knowledge and age, gender, and education. The findings affirm the value of structured teaching programmes in strengthening diabetes self-care knowledge and support their integration into routine outpatient services.